Efisiensi Komunikasi Sosial Dalam Pemasaran Digital Di Pt Perwira Chemical Perkasa - Liza Nurul Anisah; Nur Aini Anisa (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to describe the effectiveness of social media on digital marketing at PT Perwira Chemical Perkasa. Data collection techniques used are interview techniques, documentation and observation. The data analysis technique used is a qualitative descriptive technique. The results of this study are based on the ratio of the number of sales after the application of social media in digital marketing runs effectively and makes sales increase.